Pembelajaran Matematika Dengan Metode VAK (Visual Auditory Kinesthetic): Analisis Bibliometrik - Lutfiah Azzahra; Bambang Sri Anggoro; Novian Riskiana Dewi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study aims to analyze publication trends, keyword mapping, and future research opportunities related to the use of the Visual Auditory Kinesthetic (VAK) approach in mathematics education from 2014 to 2024. A descriptive quantitative method with bibliometric analysis was used. Data were collected from Google Scholar using Publish or Perish and visualized with VOSviewer. A total of 93 relevant articles were analyzed. The results show a significant increase in publications, especially during 2023–2024, with four highly cited articles reaching a total of 171 citations. Keyword mapping revealed eight clusters, with dominant terms such as kinesthetic, problem, ability, and education. Future studies are encouraged to explore the integration of the VAK approach with underexplored topics such as artificial intelligence.